A system study on the management of physical facilities at Visayas State University - Ongy, Elvira Enteri (Animo Repository, 2021)
Visayas State University (VSU) is a leading global University in agriculture and allied fields. VSU is classified as Level IV Higher Education Institution by the Commission on Higher Education and the first institution in the country to be accredited Level III by the Accrediting Agency for Chartered Colleges and Universities in the Philippines. As the University aims for excellence and world-class education, it must continually improve the effectiveness of its Quality Management System by ensuring that appropriate resources are being provided for its implementation, maintenance, and enhancement. One of the important resources of any organization is the Physical Facilities as it has a great impact on the organization. Management of physical facilities in an academic institution plays a significant role. Effective school maintenance protects capital investment, ensures the health and safety of the students and the employees, and supports educational performance. In this study, the strengths, weaknesses, opportunities, and threats of the process of the management of physical facilities at VSU were analyzed and evaluated using the WOT-SURGC methodology. Results showed that the most serious problem in the management of physical facilities that VSU is facing is the low accomplishment of the corrective maintenance process wherein a total of 310 job requests (40% of total filed job requests) were left unserved for around 374 days (total average) from July 2019 to July 2021. The low accomplishment of the corrective maintenance process was mainly attributed to the unserved or uncompleted job requests instigated by the long response lead time in conducting the corrective maintenance process. The lead time in responding to a job request from receiving to start of conduct of the corrective maintenance is about 35 days (total average) which is way far against the two (2) maximum day’s target. After clarifying and analyzing the problem using tools such as process mapping, waste identification, Pareto chart, and Kepner-Tregoe Problem Analysis, several probable causes were identified. Validation of these probable causes was performed to identify the true causes and a Why-Why methodology was used to determine the root causes. Alternative solutions were recommended to reduce the long response lead time. These solutions were then evaluated using the Kepner-Tregoe Decision Analysis tool to determine the best solutions. The proposed solutions to the problem require no additional cost to the University. The implementation plan was also provided to guide the process owners in effectively implementing the proposed system. The methodology employed in this system study can be used or adapted by the University to systemically approach a problem especially those that are related to services or transactional activities within the University.